To use or not to use? CAQDAS usage choices and practices among postgraduate sociology students - Rodik, Petra; Primorac, Jaka (2010)
Information and communication technologies (ICT) become more and more present within everyday research practices, and we tend to take them for granted. This is even more important with the contemporary ICT, because the mode of its learning and usage is more interactive ; when comparing to more ‘learn-then-use’ technologies, CAQDAS could be regarded as a prototype of ‘learn-by-usage’ technology. Its learning and usage involves a series of decisions, and the outcome of all these decisions taken together has consequences for every step of research process. This paper will present the case study research on CAQDAS usage choices and practices among postgraduate sociology students in Croatia. This case study research will be based on short surveys and in-depth interviews with the researchers who have used CAQDAS. We shall investigate: how do researchers implement new ICT for qualitative research methods in their research, or whether they do it at all? What CAQDAS software they use (and why)? Do they use the collaborative options that CAQDAS bring? What factors are most influential regarding their CAQDAS package choice? Are internal or external factors of a certain package more important for these decisions? How do the various obstacles in access to new research tools and their applicability influence the choice of their research topics? Thus, with findings of this case study, the authors of this paper aim to outline some of the reflexive influences of ICT on the research choices and practices in contemporary sociology.
Projekt MZOS
ENG